Comparative genomic analysis of two novel plasmids from Acidithiobacillus ferrivorans strain PQ33 - Ccorahua, Robert (2021)
Acidithiobacillus ferrivorans is a psychrotolerant acidophile capable of growing and oxidizing ferrous and sulphide substrates at low temperatures. To date, six genomes of this organism have been characterized; however, evidence of a plasmid in this species has been reported only once, whereby there is no conclusive role of the plasmids in the species. Herein, two novel plasmids of A. ferrivorans PQ33 were molecularly characterized and compared at a genomic scale. The genomes of two plasmids (12 kbp and 10 kbp) from A. ferrivorans PQ33 (NZ_LVZL01000000) were sequenced and annotated. The plasmids, named pAfPQ33-1 (NZ_CP021414.1) and pAfPQ33-2 (NZ_CP021415.1), presented 9 CDS and 13 CDS, respectively. In silico analysis showed proteins involved in conjugation (TraD, MobA, Eep and XerD), toxin-antitoxin systems (HicA and HicB), replication (RepA and DNA binding protein), transcription regulation (CopG), chaperone DnaJ, and a virulence gene (vapD). Furthermore, the plasmids contain sequences similar to phosphate-selective porins O and P and a diguanylate cyclase-phosphodiesterase protein. The presence of these genes suggests the possibility of horizontal transfer, a regulatory system of plasmid maintenance, and adhesion to substrates for A. ferrivorans species and PQ33. This is the first report of plasmids in this strain.